2022
DOI: 10.31234/osf.io/q4h37
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternal affect and youth psychopathology: The role of mother-adolescent affect congruency

Abstract: Maternal affect contributes to children’s psychosocial adjustment. How maternal daily affect intensity and dynamics (i.e., inertia and variability) are associated with adolescents’ concurrent and later psychopathological symptoms, however, remains unclear. This preregistered study examined (1) associations of maternal day-to-day positive and negative affect intensity, inertia, and variability with adolescent and young adult psychopathological symptoms, and (2) moderating effects of mother-adolescent affect con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…It was found that the trust of family was very high, followed by trust of school friends and teachers among adolescents. Similarly, Schulz et al (2022) have highlighted important role of mothers in everyday life of adolescents. Also, there is research evidence suggesting that maternal bonding is an important predictor of perfectionism among their children (Sabrina et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the trust of family was very high, followed by trust of school friends and teachers among adolescents. Similarly, Schulz et al (2022) have highlighted important role of mothers in everyday life of adolescents. Also, there is research evidence suggesting that maternal bonding is an important predictor of perfectionism among their children (Sabrina et al, 2023).…”
Section: Discussionmentioning
confidence: 99%